Update of the Country Procurement Assessment Review - Republic of Mozambique; World Bank (World Bank, Washington, DC, 2013)
This Country Procurement Assessment Review (CPAR) update is conducted jointly by the Mozambique Government, the World Bank (Bank), the African Development Bank (AfDB), and the donor community with a view to update the diagnostic work carried out in 2002. The update is considered highly opportune in view of the progress achieved since the last review and in consideration of the increased Government focus on monitoring the performance of Public Financial Management (PFM) reforms, including public procurement. In this context, the objectives of the CPAR have been defined as follows: (i) to assess the public procurement systems using OECD DAC Methodology, (ii) to recommend a monitoring mechanism to measure procurement systems compliance/performance and progress toward acceptable international standards, and (iii) to identify the areas of opportunity for improvement and recommend an action plan.